Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2014
DOI: 10.1155/2014/707301
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Different Catalyst Deposition Technique on Aligned Multiwalled Carbon Nanotubes Grown by Thermal Chemical Vapor Deposition

Abstract: The paper reported the investigation of the substrate preparation technique involving deposition of iron catalyst by electron beam evaporation and ferrocene vaporization in order to produce vertically aligned multiwalled carbon nanotubes array needed for fabrication of tailored devices. Prior to the growth at 700°C in ethylene, silicon dioxide coated silicon substrate was prepared by depositing alumina followed by iron using two different methods as described earlier. Characterization analysis revealed that al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(1 citation statement)
references
References 41 publications
(45 reference statements)
0
1
0
Order By: Relevance
“…However, from the XPS spectrum shown in Figure S1B, and multiple others collected in our studies (data not shown), no indication of Fe or Co was quantifiable. More specifically, no peaks for Fe or Co were observed, which normally occur in the range 700–800 eV, thus confirming the absence of noteworthy catalyst nanoparticles in the HD-CNT f. XPS for the CNT f shows peaks at 290 and 530 eV that belong to carbon 1s and oxygen 1s. The detection limit of XPS is 0.1 at.…”
Section: Resultsmentioning
confidence: 71%
“…However, from the XPS spectrum shown in Figure S1B, and multiple others collected in our studies (data not shown), no indication of Fe or Co was quantifiable. More specifically, no peaks for Fe or Co were observed, which normally occur in the range 700–800 eV, thus confirming the absence of noteworthy catalyst nanoparticles in the HD-CNT f. XPS for the CNT f shows peaks at 290 and 530 eV that belong to carbon 1s and oxygen 1s. The detection limit of XPS is 0.1 at.…”
Section: Resultsmentioning
confidence: 71%